Religious Moderation in Islamic Education Learning and Its Influence on Students’ Multicultural Attitudes in Multiethnic Areas - Murjiah Murjiah; Fahmi Hamdi; Salamah Salamah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This article examines the relevance of religious moderation in Islamic Religious Education (PAI) learning to the formation of multicultural attitudes among students, particularly in multiethnic regions such as Balangan Regency, South Kalimantan. Using an integrative literature review approach, this study analyzes the relationship between the concept of religious moderation (tawassuth, tawazun, i'tidal, tasamuh) and the dimensions of multicultural attitudes as framed by James A. Banks. Bronfenbrenner's Ecological Theory is employed as a meta-theory to understand the position of PAI learning as an agent of value socialization within the school microsystem. Findings indicate that PAI learning that consistently and contextually integrates moderation values is both relevant and effective in building students' multicultural attitudes across cognitive, affective, and conative dimensions. PAI teachers who serve as role models (uswah hasanah) for inclusive values and employ dialogical and cooperative learning methods function as the most strategic transformative agents. The implications of this study affirm the necessity of reformulating PAI learning approaches from doctrinal transmission toward contextual and participatory value internalization, especially in regions with complex multiethnic compositions outside Java